DISTRIBUSI KEUNTUNGAN YANG ADIL ANTAR AKTOR RANTAI PASOK AGROINDUSTRI SAGU DI KABUPATEN KEPULAUAN MERANTI, RIAU - Yusmiati Yusmiati; Machfud Machfud; Marimin Marimin; Titi Candra Sunarti (Department of Agroindustrial Technology, Bogor Agricultural University, 2023)
The distribution of benefits among supply chain actors is complex and full of challenges because various factors, including uncertainty, influence it. This study aims to solve the problem of profit distribution to produce a fair profit distribution among supply chain actors by incorporating elements of uncertainty, risk, and value-added. The model of fair profit distribution is made using the cooperative game theory approach with fuzzy Shapley values, which incorporates the elements of uncertainty in profit, risk, and added value. The fair profit distribution between supply chain actors is validated in the sago agro-industry supply chain in the Meranti Islands Regency. The risks of each supply chain actor were obtained using the fuzzy analytical hierarchy process technique, with risk values of 0.52, 0.23, 0.2, and 0.29 for farmers, traders, wet starch agro-industries, and dry starch agro-industries, respectively. While the value-added ratio of each supply chain actor is 12%, 35.92%, 13.9%, and 15.1%, respectively, as obtained by the Hayami method. The model validation results show that the fair profit distribution to farmers is 17.77%, to traders it is 29.69%, to the wet starch agro-industry it is 9.91%, and to the dry starch agro-industry it is 42.63% of the total supply chain profits. This result is more proportional than the current profit distribution, which is respectively 10.03%, 15.29%, 1.7%, and 72.98%. These results are considered fairer and more proportional because they take into account the uncertainty of the benefits, risks, and added value of each actor in the sago agro-industry supply chain. Keywords: fair profit distribution, fuzzy Shapley value, sago agro-industry, supply chain, uncertainty